Re-evaluating Fiqh Methodology: Toward a Contextual Islamic Legal Framework Responsive to Global Social Transformations - Prasetyo Hartanto; Ansor Lubis (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2024)
This study explores the re-evaluation and re-shaping of fiqh methodology to ensure Islamic law remains relevant and responsive to contemporary issues. As society evolves, new challenges such as migration, the digital economy, and shifting moral standards present complex legal and ethical dilemmas that traditional fiqh struggles to address. Contextual fiqh, which integrates classical Islamic principles with modern social, economic, and technological developments, offers a dynamic approach to Islamic law that addresses these challenges. The study emphasizes the flexibility of contextual fiqh in offering more adaptable legal solutions, particularly in the realms of migration, digital transactions, and family law. By incorporating modern social dynamics, including technological advancements like cryptocurrencies and virtual marriages, contextual fiqh proposes a legal framework that is both grounded in Islamic principles and relevant to contemporary needs. The research highlights the importance of interdisciplinary engagement between Islamic scholarship and fields such as economics, sociology, and technology, offering a holistic approach to legal decision-making. Through the examination of case studies, such as the application of Islamic legal principles to global migration patterns and digital financial systems, the study demonstrates how contextual fiqh can provide ethical and practical solutions to modern problems. The findings suggest that the adoption of contextual fiqh can lead to more inclusive, just, and responsive legal frameworks, making Islamic law more adaptable and effective in addressing the complexities of the modern world.